Severe Acute Respiratory Syndrome Coronavirus 2 Anti-Spike Antibody Levels Following Second Dose of ChAdOx1 nCov-19 or BNT162b2 Vaccine in Residents of Long-term Care Facilities in England (VIVALDI). (16th April 2022) - Stirrup, Oliver; Krutikov, Maria; Tut, Gokhan; Palmer, Tom; Bone, David; Bruton, Rachel; Fuller, Chris; Azmi, Borscha; Lancaster, Tara; Sylla, Panagiota; Kaur, Nayandeep; Spalkova, Eliska; et al.
Abstract: General population studies have shown strong humoral response following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination with subsequent waning of anti-spike antibody levels. Vaccine-induced immune responses are often attenuated in frail and older populations, but published data are scarce. We measured SARS-CoV-2 anti-spike antibody levels in long-term care facility residents and staff following a second vaccination dose with Oxford-AstraZeneca or Pfizer-BioNTech. Vaccination elicited robust antibody responses in older residents, suggesting comparable levels of vaccine-induced immunity to that in the general population. Antibody levels are higher after Pfizer-BioNTech vaccination but fall more rapidly compared to Oxford-AstraZeneca recipients and are enhanced by prior infection in both groups. Abstract : Antibody responses to vaccination in older residents of long-term care facilities are comparable to those in the general population. Although antibody levels are initially greater, they fall more rapidly following Pfizer-BioNTech vaccination than Oxford-AstraZeneca. Prior infection enhances responses in both groups.